Optimization of Genetic Material Extraction Techniques and Application of Isothermal Amplification Method for Field Authentication of Two Thresher Sharks (Alopias pelagicus and Alopias superciliosus) - Aldina, Vatia Dwi Rizki Ramadhani; Abdullah, Asadatun; Rianti, Puji; Jacoeb, Agoes Mardiono (HAYATI Journal of Biosciences, 2025)
The pelagic thresher shark (Alopias pelagicus) and bigeye thresher shark (Alopias superciliosus) are important shark species for Indonesia's consumption and finning industry. Both Alopias species are included in the CITES appendix II, thus requiring certain documents for trading. Regarding species identification for on-site application, the DNA isolation method is a crucial step. In this study, we developed a DNA isolation method suitable for on-site application based on isothermal amplification (LAMP) and species-specific COI gene markers. Three different extraction methods were applied, namely modified spin column kits and dipsticks. The quality of DNA was evaluated and tested for isothermal amplification using a reference sample, fresh fillet, and ethanol-preserved sample. The extracted sample concentration was in the range of 135.35-0.65 ng/μL. The LAMP test showed that three different DNA extraction methods successfully amplified the DNA fragments through the color changes at the end point of the LAMP reaction. The LAMP test was also sufficient to detect less than 10 ng of DNA from A. pelagicus and A. superciliosus within 30-50 min. The DNA from the modified spin column and dipstick extraction method combined with LAMP can potentially be used to detect Alopias pelagicus and Alopias superciliosus species on-site.